Glycogen synthase kinase-3-mediated phosphorylation of serine 73 targets sterol response element binding protein-1c (SREBP-1c) for proteasomal degradation. Issue 1 (15th January 2016) - Dong, Qingming; Giorgianni, Francesco; Beranova-Giorgianni, Sarka; Deng, Xiong; O'Meally, Robert N.; Bridges, Dave; Park, Edwards A.; Cole, Robert N.; Elam, Marshall B.; Raghow, Rajendra
Abstract : We have identified Serine 73 as a novel GSK-3β site on SREBP-1c that alters its affinity for SCAP, and proteasomal degradation. Phosphorylation of Serine 73 by GSK-3β during starvation (insulin-depleted stat) may lead to lower levels of SREBP-1c; conversely, de-phosphorylation of this site may be involved in stabilizing SREBP-1c by insulin (by blocking GSK-3β action). A functional role of this site needs to be corroborated in vivo . Abstract : Sterol regulatory element binding protein-1c (SREBP-1c) is a key transcription factor that regulates genes involved in the de novo lipid synthesis and glycolysis pathways. The structure, turnover and transactivation potential of SREBP-1c are regulated by macronutrients and hormones via a cascade of signalling kinases. Using MS, we have identified serine 73 as a novel glycogen synthase kinase-3 (GSK-3) phosphorylation site in the rat SREBP-1c purified from McA-RH7777 hepatoma cells. Our site-specific mutagenesis strategy revealed that the turnover of SREBP-1c, containing wild type, phospho-null (serine to alanine) or phospho-mimetic (serine to aspartic acid) substitutions, was differentially regulated. We show that the S73D mutant of pSREBP-1c, that mimicked a state of constitutive phosphorylation, dissociated from the SREBP-1c–SCAP complex more readily and underwent GSK-3-dependent proteasomal degradation via SCF Fbw7 ubiquitin ligase pathway. Pharmacologic inhibition of GSK-3 or knockdown of GSK-3 by siRNA prevented accelerated degradation of SREBP-1c. As demonstrated by MS, SREBP-1c was phosphorylated in vitro by GSK-3β at serine 73. Phosphorylation of serine 73 also occurs in the intact liver. We propose that GSK-3-mediated phosphorylation of serine 73 in the rat SREBP-1c and its concomitant destabilization represents a novel mechanism involved in the inhibition of de novo lipid synthesis in the liver.